INFLAMMATORY INFILTRATION IN THE GASTRIC MUCOSA OF PATIENTS WITH EPSTEIN-BARR VIRUS-ASSOCIATED GASTRIC DYSPLASIA AND CANCER - М. V. Vusik; R. I. Pleshko; Т. V. Avdeenko; О. V. Cheremisina; L. N. Urazova; N. V. Yunusova (Сибирский онкологический журнал, 2016)
Characteristics of inflammatory infiltrate in the gastric mucosa of patients with gastric dysplasia (n=56) and gastric cancer (n=50) with different levels of humoral immune response to Epstein-Barr virus (EBV) and EBV viral load were studied. In patients with dysplasia of the gastric mucosa, the increase in antibody titers to VCA IgG leaded to a significant decrease in the level of lymphocytes, neutrophils and macrophages and an increase in the number of eosinophils and plasma cells. When the levels of IgA to viral capsid antigen (VCA) and IgG to EBV early antigens (EA) were increased, the number of neutrophils in the composition of the cellular infiltrate was significantly decreased. In gastric cancer patients with different levels of humoral immune response to EBV, the number of plasma cells and eosinophils in the inflammatory infiltrate of the tumor was decreased when increasing the titers of IgG to VCA and IgA to VCA. When VCA/IgA titer was high, the number of neutrophils in a tumor was decreased and the proportion of macrophages was slightly increased. The data obtained can serve as additional criteria for indentifying markers for viral infection of the gastric mucosa.